Contribution of TRPC Channels to Intracellular Ca2 + Dyshomeostasis in Smooth Muscle From mdx Mice - Lopez, Jose R.; Uryash, Arkady; Faury, Gilles; Estève, Eric; Adams, Jose A. (Frontiers in Physiology, 2020)
Duchenne muscular dystrophy (DMD) is an irreversible and severe muscle wasting X-linked genetic disease characterized by a progressive loss of muscle function, decreased ambulation, and ultimately death as a result of cardiac or respiratory failure. DMD is caused by the lack of dystrophin, a protein that is important for membrane stability and signaling in excitable cells. Although vascular smooth muscle cells (VSMCs) dysfunction occurs in many pathological conditions, little is known about vascular smooth muscle function in DMD. We have previously shown that striated muscle cells, as well as neurons isolated from dystrophic (mdx) mice have higher intracellular Ca2+ ([Ca2+]i) and Na+ ([Na+]i) concentrations and decreased cell viability in comparison with wild type (Wt). Experiments were carried out in isolated VSMCs from mdx (a murine model of DMD) and congenic C57BL/10SnJ Wt mice. We found elevated [Ca2+]i and [Na+]i in VSMCs from mdx mice compared to Wt. Exposure to 1-oleoyl-2-acetyl-sn-glycerol (OAG), a TRPC3 and TRPC6 channel activator, induced a greater elevation of [Ca2+]i and [Na+]i in mdx than Wt VSMCs. The OAG induced increases in [Ca2+]i could be abolished by either removal of extracellular Ca2+ or by SAR7334, a blocker of TRPC3 and TRPC 6 channels in both genotypes. Mdx and Wt VSMCs were susceptible to muscle cell stretch-induced elevations of [Ca2+]i and [Na+]i which was completely inhibited by GsMTx-4, a mechanosensitive ion channel inhibitor. Western blots showed a significant upregulation of TRPC1 -3, -6 proteins in mdx VSMCs compare to age-matched controls. Our results provide evidence that the lack of dystrophin in mdx VSMCs produced a profound alteration of [Ca2+]i and [Na+]i homeostasis that appears to be mediated by TRPC channels. Moreover, we have been able to demonstrate an enhanced stretch-induced elevation of intracellular [Ca2+] and concomitant cell damage in mdx VSMCs that also appears to be mediated through TRPC1, -3 and -6 channel activation.